Positive Self-Talk in Adolescent: A Systematic Literature Review - Mulawarman, Mulawarman; Antika, Eni Rindi; Hariyadi, Sigit; Ilmi, Achmad Miftachul; Prabawa, Abi Fa’izzarahman; Pautina, Amalia Rizki; Chairunnisa, Dini; Benu, Kristin Melliyati; Nadhita, Galuh; Lathifah, Alvia Ainil; Yuliana, Vita (Bulletin of Counseling and Psychotherapy, 2024)
This study synthesizes the literature on positive self-talk in adolescents. The research aimed to comprehensively understand descriptive forms and strategies to increase positive self-talk in adolescents. The method used in this research was Systematic Literature Review (SLR) by searching relevant articles through Scopus, Taylor & Francis Group, and Sage databases. The search was limited based on predetermined inclusion criteria, and 30 articles were obtained by peer review. The research design used was Preferred Reporting Items for Systematic Reviews and Meta-Analytics (PRISMA). The results demonstrated that the form of positive self-talk in adolescents varies and can be applied to cultivate self-talk habits that are goal-directed, rational, affective, cognitive, motivational, and have psychological functions. Strategies to improve self-talk include using gestures through repetitive practice, mental rehearsal, cognitive interventions, and using first or second-person pronouns. Furthermore, strategies to increase self-talk can be implemented using video modelling examples and naturalistic videos.